Cross-Domain Fusion Constellation Design of Communication, Navigation and Remote Sensing - Junxiang Qin; Xuan Li; Xiaotian Ma; Xiye Guo; Jun Yang (Applied Sciences, 2023)
Low earth orbit (LEO) mega-constellations have once again triggered a wave of space-based system construction. On the one hand, LEO communication, LEO navigation, LEO remote sensing constellations and so on are proposed. On the other hand, with the continuous development of software-defined satellite and intelligent satellite technology, space-based systems are developing in the direction of multi-function, integration and cross-domain integration. The whole space-based system is no longer the traditional working mode of a single functional constellation, but a genral cross-domain fusion constellation (CDFC) system for complex tasks. Like the terrestrial global Internet, the space-based system will serve as a global infrastructure for integrating communication, navigation and remote sensing, that is, the intelligent space-based system, to provide services for the global demand. The traditional method of designing constellation for a certain type of function is no longer applicable to this type of constellation design. To solve this problem, this paper proposes a design and optimization method of cross-domain fusion constellation of communication, navigation and remote sensing based on reverse design. The paper optimizes the CDFC through resource coverage. Through experiments, we prove that the number of satellites in the CDFC can be reduced by 30.60% compared with the independent and combined constellations in each domain, and the coverage and service performance of the constellation can be improved. The cost can be reduced by 18.31% compared with the combined constellation. When the same number of satellites is used, the resource coverage of the cross-domain fusion constellation is increased by at least eight times.